Curriculum development - Enstroem, Rickard (My University, 2026)
Curriculum development is the process of establishing the structure and content that equip students with knowledge and competencies to meet academic, professional, and societal demands. This chapter examines the foundational theories, processes, and frameworks that guide curriculum development in higher education. It addresses the role of stakeholders in aligning curricula with institutional priorities, educational trends, and the needs of learners. Future directions in curriculum development are considered, focusing on adaptive technologies, competency-based learning, and strategies for integrating transversal competencies within scalable frameworks.
Keywords: competency-based education; curriculum design; curriculum development; curriculum evaluation; curriculum models; educational frameworks; educational trends; higher education; learning objectives; learning outcomes; needs assessment; program assessment; stakeholder involvement